The Liquidity Premium in China’s Corporate Bond Market: A Stochastic Liquidity Discount Approach - Min, Xiaoping; Ji, Min (Risks (Basel), 2022)
China’s bond market has been ranked third globally; however, China’s corporate bonds are significantly less liquid than its stocks. Liquidity risk is an important component in China’s corporate bond spreads. In this paper, we propose a stochastic liquidity discount factor model to evaluate the liquidity risk premium and its term structure in China’s corporate bond market. The Monte Carlo simulation technique is used to quantify the impact on the liquidity premium of various liquidity factors: the liquidity level, liquidity volatility, liquidity shock, and the liquidity elasticity. Our findings conclude that the liquidity level is the most significant component of a liquidity premium. The impact on the liquidity premium of other liquidity factors is all conditional on the liquidity level. In addition, the impact of liquidity shocks and volatility is also subject to the market’s equilibrium mechanism. Further, the term of a bond affects the premium both directly and indirectly through its influence on a bond’s liquidity.